Growth factor analysis in children with nonsyndromic orofacial clefts: a systematic review - Ul Huqh, Mohamed Zahoor; Yaacob, Hashim; Veerabhadrappa, Suresh Kandagal; Abdullah, Johari Yap; Dowlath Saheb, Samiullah; Quadri, Syed Altafuddin; Marya, Anand; Selvaraj, Siddharthan (BioMed Central Ltd., 2026)
Background Orofacial clefts (OFCs) are one of the most prevalent congenital abnormalities that affect the lip and/ or palate and can cause significant growth retardation in newborns. Several studies have revealed that children with congenital defects or genetic syndromes have their own growth pattern, which may differ from that of normal children. However, during infancy and until around age two, these babies usually show a period of catch-up growth in length, weight, and head circumference for both boys and girls. It was noted out that both genders had smaller physical dimensions than normal children. In order to partially elucidate the biological mechanism affecting children with non-syndromic OFCs, this systematic review aims to assess the relative expression and localization of growth factors and their receptors in craniofacial tissues. Method A comprehensive literature search was carried out on May 1, 2025, using three important databases: Web of Science Core collection, PubMed, and Scopus. The search was limited to only English-language studies involving human subjects, but it was not limited by publication date. To find potentially relevant publications, specific keywords and database-specific search techniques were used. Results Based on predefined inclusion criteria, 20 studies were selected from a total of 191 articles following a thorough screening process. Growth factors and susceptibility to OFCs were found to be significantly correlated in the analysis of the reports of the chosen studies. Particularly, OFCs and their risk were consistently associated with fibroblast growth factor receptor (FGFR1) and transforming growth factor (TGFβ3). More angiogenesis in compromised tissues is suggested by the elevated levels of two angiogenesis-related proteins, vascular endothelial growth factor (VEGF) and Cluster of differentiation (CD34). Similarly, the studies that used unilateral samples showed relatively high levels of TGFβ3, FGFR1, and bone morphogenetic protein (BMP2/4), which were also higher in bone cells, connective tissues, and epithelia. Conclusion The reviewed studies indicate a role of growth-related proteins in the pathophysiology of nonsyndromic OFCs. This is demonstrated by the fact that FGFR1 is higher in all studies, TGFβ3 is upregulated in all the studies, and angiogenesis markers (VEGF and CD34) are consistently higher in cases. Additional investigation is needed to determine whether FGFR1 and TGFβ3 can serve as biomarkers or targets for intervention in OFC-related abnormalities.